Using typographic patterns in commercial advertising design: عصام إبراهيم محمد الكبيسي (Al-Academy, 2021)
Typographic patterns are one of the design elements in commercial advertising for their ability to deliver the message and information to the recipient smoothly and quickly, and it is indicated that there are many different techniques that can use typographic patterns in commercial advertisements, including spacing, spaces between letters, letter height, length, weight, and contrast and this Usage must be studied according to the type of font and how it can be used in advertising campaigns.Based on the above, the research came to study (employing typographic patterns in commercial advertising design) in which the researcher identified his question for the purpose of reaching a solution to his research problem which is (Is it possible to employ typographic patterns to be used as a basic element in designing the advertising idea for commercial advertising to achieve functional, aesthetic and expressive values? It also included the importance of research and limitations as well as the definition of terminology.As for the theoretical framework, the literature related to the research topic was reviewed to include the concept of typography, and the functional dimension of typographic patterns, and it was concluded with the indicators of the theoretical framework.As for the research procedures, the researcher adopted the descriptive approach, the method of analyzing the content in the analysis procedures, in order to achieve the goal of the research, as the research community came to be represented by the products of international advertising agencies and for the large number of advertisements issued by them, the researcher decided to approve the designs issued by them and chose the designs of printed advertisements only and issued by them for the year 2018.And the last of this research, the results and conclusions were reviewed, the most important of which are:1. The result of the use of three-dimensional letters has the ability to attract the consumer more than the two-dimensional lettering.2. Changing the typographic character, size, weight, color, and position changes the way the message appears and often changes the meaning.He concluded with recommendations, proposals and sources